Dampak Penerapan Akuntansi Forensik Dan Audit Investigasi Serta Mengevaluasi Proses Pengungkapan Tindak Pidana Fraud Pengadaan Barang/Jasa - Alya Syafikah Rani; Radina Amalia Maharani; Nera Marinda Machdar (Universitas 45 Surabaya, 2024)
As a result of the forensic accounting and investigative audit processes as well as procedures for detecting criminal acts related to the procurement of goods and services, fraud occurred related to community needs as follows: Procurement of goods and services. This usually happens in Indonesia. This research uses the Partial Least Squares (PLS) analysis technique and the SmartPLS 3.2.8 software testing tool. The results show that forensic accounting practices and investigative audit results influence the detection rate of fraud in the procurement of goods and services.